Advances in nuclear emission PET and SPECT imaging. - Garcia, E.V (IEEE Engineering in medicine and biology magazine)
Improvements in technology and methods have resulted in a field that is ready to unlock the body's secrets. The advancements reviewed in this article are remarkable. Just ten years ago, SPECT myocardial tomograms exhibited a spatial resolution of close to 2 cm and PET scanners were prohibitively expensive. The instrumentation reviewed can image down to a 1.8 mm spatial resolution, and high-performance PET scanners and PET/SPECT cameras are being routinely sold for one-third the cost of the high-end PET scanners of ten years ago. These gains, coupled with the relative ease of developing positron-emitting radiopharmaceuticals, opens a new chapter in physiologic imaging. Add to this that these modalities are inherently digital, facilitating their progress in totally automatic analysis; multidimensional, multimodality display; and computer-assisted image interpretation by the use of AI techniques. The result is a field poised to unlock the secrets of the body's functions, when the only limitation is one's own imagination and the number of scientists working to bring it to its full potential